Characteristics of Soil Chemical Properties in Several Types of Oil Palm (Elaeis guineensis Jacq.) Land and Shrubs in Negeri Lama Seberang Village (Case Study of Lower Bilah Watershed) - Julfan Julfan Efendi Nasution; Fitra Syawal Harahap; Ika Ayu Putri Septyani; Badrul Ainy Dalimunthe (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The Bilah Sub-Watershed area includes areas that have somewhat critical or semi-critical land so that land use is the result of human efforts in managing the available resources to meet their various needs. This often results in land use not being in accordance with its capabilities. This research aims to examine the chemical properties of several vegetation in Negeri Lama Seberang Village, Bilah Hilir District, Labuhanbatu Regency. The research was carried out from December to March 2024 using a survey method. Soil samples were taken at 3 points for each vegetation and different slopes at depths of 1-10 cm and 10-20 cm using a simple random method. The soil parameters measured were soil acidity (electrometry), soil organic carbon content (Walkley and Black), and soil texture (bouyoucos hydrometer). Soil analysis was carried out at the Laboratory of the Faculty of Agriculture, University of North Sumatra. The results of this research show that on a slope of 0-8% the average soil pH value is 4.61% and organic C is 1.04%, while on a slope of 8-15% the average soil pH value is 4.46% and C -organic 0.91%. On a slope of 0-8% the average value of the clay fraction is 20.27%, the dust fraction is 15.02% and the sand fraction is 64.41%, while on a slope of 8-15% the average value of the clay fraction is 27.48%, the dust fraction 19.87%, and sand fraction 52.63%.